Investigating the Impact of Online Media on Agricultural Practices and Rural Development: A Content Analysis - K, Geethalakshmi; Thaloor, Saranya; Gajare, Priyanka (Indian Journal of Extension Education, 2024)
Agriculture, the primary sector of India, supporting the livelihoods of over 50% of the population, has undergone rapid modernization, highlighting the need for effective networking and knowledge dissemination among key stakeholders: farmers, policymakers, researchers, and entrepreneurs. However, due to the sector’s reliance on traditional practices, an observable information gap can be seen in terms of adopting regenerative farming techniques, sustainability, policy support, and innovation. Several online media contents on agriculture and farming practices were examined using content analysis for this study, and coding was done based on three primary factors: content, message style, and interactive elements. Six sub- dimensions were coded within the content dimension, including relevance, frequency, circulation, reach, quality and audience interaction. This study held in 2024, conducted a qualitative content analysis of agricultural digital platforms to evaluate their effectiveness in bridging the gap between the farming stakeholders. The findings suggest that digital media is an effective tool for amplifying farming and rural upliftment efforts through science communication, improving information accessibility, and sustainability in the agricultural community. The role of social media among digital platforms is also showing a tremendous increase in creating scientific temper among farming communities.